2018
DOI: 10.1071/wr18009
|View full text |Cite
|
Sign up to set email alerts
|

Livestock depredation by large carnivores in the South Gobi, Mongolia

Abstract: Context Livestock depredation is a major conservation challenge around the world, causing considerable economical losses to pastoral communities and often result in retaliatory killing. In Mongolia, livestock depredation rates are thought to be increasing due to changes in pastoral practices and the transformation of wild habitats into pasture lands. Few studies have examined the interactions between humans and carnivores and even fewer have considered how recent changes in pastoral practices may affect depred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…The preference for pumas for rocky and vegetation cover is likely, in addition to the fact that they usually avoid areas inhabited by humans (Dellinger et al 2020). Similar patterns of a positive correlation between ranch size and/or livestock numbers and predator attacks have been widely reported for a large number of predator species both in America (Mech et al 2000;Treves et al 2004;Bradley and Pletscher 2005;Romero-Muñoz et al 2016;Sarmiento-Giraldo et al 2016), as elsewhere (Kaartinen et al 2009;Hanley et al 2018;Mijiddorj et al 2018).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The preference for pumas for rocky and vegetation cover is likely, in addition to the fact that they usually avoid areas inhabited by humans (Dellinger et al 2020). Similar patterns of a positive correlation between ranch size and/or livestock numbers and predator attacks have been widely reported for a large number of predator species both in America (Mech et al 2000;Treves et al 2004;Bradley and Pletscher 2005;Romero-Muñoz et al 2016;Sarmiento-Giraldo et al 2016), as elsewhere (Kaartinen et al 2009;Hanley et al 2018;Mijiddorj et al 2018).…”
Section: Discussionsupporting
confidence: 75%
“…The single most important variable that may be controlled through management practices is husbandry, whose rate of increase is related to a decrease in the probability of receiving an attack from culpeo foxes. Husbandry and herding have been repeatedly found to reduce predator attacks in previous studies elsewhere (Conover 2002;Treves et al 2002;Treves and Karanth 2003;Ogada et al 2003;Treves et al 2006;Mijiddorj et al 2018;Adhikari et al 2020). Two other variables that were negatively related to the likelihood of fox attacks were livestock biomass and area covered by Bofedales.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, community's perceptions about Snow leopards were less negative compared to wolves, possibly due to conservation programs or awareness-raising in the community about Snow leopards. A study in Mongolia found a similar situation, where the community had stronger negative perceptions on wolves than on Snow leopards [65].…”
Section: Trophy Hunting: Its Impacts On Carnivoresmentioning
confidence: 84%
“…Livestock depredation is worsened in our study areas because husbandry is often lax during herding seasons (Suryawanshi et al, ) which, exacerbating the threats, coincide with the breeding seasons of the Himalayan wolf (Feb–Jun) (Werhahn, Kusi, et al, ) and snow leopard (Jan–Jun) (McCarthy et al, ). Our respondents offered suggestions for improving herding practices, such as keeping livestock in larger herds attended by sufficient herders and avoiding known predation hotspots; that these obvious measures are in the villagers' minds, and yet not implemented is a symptom of the cognitive dissonance characteristic of human–wildlife conflict (see also Mijiddorj, Alexander, & Samelius, ). Herders' declared need for training can be met by demonstration of the construction of robust, durable, predator‐proof, livestock corrals used to protect herds at night using locally available stones to build high walls in combination with wire netting especially for the open top (see Jackson & Wangchuk, ).…”
Section: Discussionmentioning
confidence: 99%